Respostas
respondido por:
1
a) (-3x³y²).(5x⁴y⁵) = -15x³⁺⁴y²⁺⁵ = -15x⁷y⁷
.......2...................4..................8............................8
b) ( ----a²b³c⁴) . ( ----a³b⁴c⁸) = ----a²⁺³b³⁺⁴c⁴⁺⁸) = ----a⁵b⁷c¹²
.......3...................7..................21.........................21
c) (x⁴y) : (x²y) = x⁴⁻²y¹⁻¹ = x²y
......... 3 .............. 2
d) (- ---a⁵b²) : ( ---a³b) =
.........4 .............3
..... 3 ........... 3 ............9 .................. 9
(- ---a⁵b²) . ( ---a³b) = -----a⁵⁺³b²⁺¹ = ----a⁸b³
.....4 ............ 2 .............8 ..................8
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás